Orbital Expansion in Cranial Vault After Minimally Invasive Extradural Transorbital Decompression for Thyroid Orbitopathy. Issue 1 (January 2019) - Ramesh, Sathyadeepak; Nobori, Alexander; Wang, Yi; Rootman, Daniel; Goldberg, Robert Alan
Abstract : Purpose: To test the hypothesis that the orbit expands in the cranial vault after wide dural exposure after minimally invasive extradural transorbital decompression for thyroid eye disease. Methods: A cross-sectional cohort study of 36 patients (60 orbits). Preoperative and postoperative (6 months) orbital CT following extradural transorbital decompression was analyzed. Primary outcome measure was the percentage area of the cranial vault occupied by orbital and brain tissue in a predefined window before and after surgery. Secondary outcome measures were displacement of the anteriormost aspect of the temporal lobe, reduction in clinical proptosis, change in clinical activity score, and change in diplopia. Results: The mean percentage of the selected area of the cranial vault preoperatively was 0% orbital and 44% ± 15% brain tissue, compared with 70% ± 16% orbital and 28% ± 14% brain tissue postoperatively ( p < 0.001). Posterior movement of the brain was demonstrated in 59 of 60 orbits, with a mean displacement of 2.0 mm ± 1.3 mm ( p < 0.001). Mean proptosis reduction was 11.2 mm ± 3.6 mm ( p < 0.001). The proportion of patients with clinical activity score <3 compared with clinical activity score ≥3 was not significantly different after surgery ( p = 0.163). Improved diplopia was noted in 5 patients (14%), and worsening diplopia was noted in 3 patients (8%), although these changes were not significant ( p = 0.772). Intraoperative dural tear with cerebrospinal fluid leak was reported in 2 orbits (3%), which was successfully managed with fibrin glue, with no sequelae. No other complications were noted, including infection, spontaneous orbital pulsations, postoperative hemorrhage (intracranial or intraorbital), or reactivation of disease. Conclusion: With wide exposure of the middle cranial fossa dura following extradural transorbital decompression, orbital tissue typically expands in the cranial vault. Abstract : The orbit expands in the cranial vault after wide dural exposure in deep lateral and medial decompression for thyroid orbitopathy.Supplemental Digital Content is available in the text.